Legal Remedies of Victim of Online Sales and Buying Fraud and Authority To Block Account of Criminal Banks - Annas Huda Sofianuddin; Ferry Hary Ardianto; Sulfikar; Eko Budisusanto (Faculty of Law, Merdeka University Surabaya, 2021)
Information technology has grown rapidly lately, especially in the internet media. There are so many positive benefits with the presence of this internet media, which is that it can simplify one's work or communication, including buying and selling which is usually done face-to-face, which is now sufficient through the internet media Even though it has a positive impact, buying and selling online also has a negative impact, namely that someone can commit fraud. There have been many victims as a result of online buying and selling fraud committed by irresponsible individuals or parties so that it is hoped that this article can provide insight and knowledge to practitioners and the general public regarding what legal measures can be taken to restore their rights. This article uses a normative juridical writing method with a statutory approach and a conceptual approach. The result of this writing is that if someone feels aggrieved and is a victim of online buying and selling fraud, that person can make a police report and then can submit an application to the bank to block the account of the criminal buying and selling online.